Maria Moog-Grünewald (ed.), Brill‘s New Pauly. Supplements 4. The Reception of Myth and Mythology (Leiden-Boston: Brill, 2010) - Giorgio Baruchello (Nordicum-Mediterraneum, 2011)
Book review of the fourth supplement in Brill's New Pauly.